Citra Diri dan Popularitas Artis - Esther Meilany Pattipeilohy (Institut Agama Islam Negeri (IAIN) Curup, 2016)
The purpose of this study is to determine how artist's self-image is displayed in media, and how an artist prepares him/herself. This study also aims to know how the artists understand their popularity as the result of news delivered by journalists in mass media. The method used in this study is a qualitative method with dramaturgicaltheoryapproach. Dramaturgy is actually under a larger perspective which is often called by phenomenological perspective or interpretive perspective. The results of this study indicate that self-image for the artist determines the impression to be formed in the mass media. The better self-image displayed, the bigger chance to get a good impression will be achieved. Before dealing with a reporter for an interview, the artist did some preparations, such as be neat and dressing up, cool their self down in order to be in a good or stable emotions, and have a discussion with the management to show a positive self-image in front of journalists. Artists fullyunderstandthe meaning of popularity for themselves.The positive popularity will also give a positive effect. Meanwhile, if they gained negative popularity, it will impact to contract termination with third parties, loss of earning opportunities through advertisement,off air, losing fans,etc. This displayed self-image, if delivered positively by journalists in news, it will give a positive